Peelable thin films for implants and cosmetics - Xu, David Tong Chern (Nanyang Technological University, 2024)
Peelable thin films are of significant importance in the fields of cosmetics and wound dressings, since they require special performance characteristics including exceptional resistance to moisture, long-lasting properties, and compatibility with biological systems. Nevertheless, current commercial bioadhesives frequently demonstrate compromises between these crucial characteristics, limiting either the ability to adhere to tissues or their cohesive strength. This study seeks to investigate the connections between the structure and properties of acrylate hybrid polymer formulations that are initiated by diazirines when exposed to 365nm ultraviolet A (UVA) light. Diazirines, renowned for their inherent biocompatibility and solubility in organic formulations, present considerable potential as substitutes for traditional photoinitiators such as TPO as they do not produce toxic by-products. This study aims to thoroughly analyse and quantify distinct structure-property relationships using photorheometry as a methodological approach. The manipulation of hybrid acrylate mixtures that consist of both mono-functional and di-functional acrylates can tailor mechanical properties such as complex modulus and elongation characteristics of the resulting films. PEGMEA introduced into PEGDA blends showed a positive trend in improving toughness from 1.2 MPa (PEGDA:PEGMEA 50:50) to 6.2 MPa (PEGDA:PEGMEA 20:80) but was found to not have any statistical difference. ANH2 was also found to not have statistical difference in improving complex modulus in PEGDA:ANH2 blends, indicating an average of ~10MPa. PEGMEA:ANH2 blends were crosslinked with PEGDA to increase G* from 176kPa (0% PEGDA) to 1.6MPa (3% PEGDA). 405nm light can be also employed initiate free radical polymerisation of acrylate blends. Peel tests were also conducted for PEGMEA:ANH2 43:57 blends to test their adhesion strength and was noted to have a peel strength of 446 N/m. By addition of PEGDA in small concentrations into the formula, the peel strength dropped significantly to below 100 N/m. Swell tests for PEGMEA:ANH2 formulations showed a swell ratio of 1280%. A polymerization temperature profile test was conducted, and it was reported that the radical polymerization of acrylates can reach 100 °c during the initial 10 seconds after curing, possibly causing thermal trauma to the surrounding area.